TASK OF SPEECH THERAPIST IN THE CARE OF NEWBORN BABIES WITH SUCKING PROBLEMS - Tabachova, Jana; Vitásková, Kateřina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
This article points to the importance of speech therapy already in the neonatal period. When a baby is born, he should be equipped with primary reflexes that allow us to survive (e.g. sucking and swallowing).Food intake and physiological sucking is a prerequisite for adequate development of oral motor functions. If baby is no able to suck or suction is insufficient, we stop the breastfeeding and the baby is feeding by alternative method like nursing bottle, syringe or nasogastric tube. Mother often will not return to the breastfeeding. The task of the speech therapist is using stimulation to active sufficient sucking reflex and using the child to swallow properly. When baby has no problem with swallowing, he constitutes a prerequisite for the proper development of oral motor functions and consequently speech. In the introduction of this article we deal with the theoretical definition of the problem- the classification of newborn, development of sucking and swallowing, the importance of breastfeeding. In the second part of this article we write about stimulation of sucking and swallowing in high birth weight infants and low birth weight infants. Data were obtained through interviews with parents, they completed anamnestic questionnaire, therapists observed and works with babies.